Anatol Konse (1898–1937/38) – anarchista, poeta, „element społecznie niebezpieczny” - Łaniewski, Aleksander (Instytut Historii PAN, 2025)
The article discusses the life, activities and work of the forgotten anarchist poet of Polish-Belarusian origin, Anatol’ Konse (1898–1937/38). The tragic fate of the forgotten revolutionary is set against the backdrop of the era, the intensification of repression by the Soviet power apparatus, and within the context of the political practice of the anarchist movement in the USSR during the 1920s and 1930s, as well as its connections with foreign representatives of anarchism.
p. 5-27
Summary in English
Keywords: Konse, Anatol' (1898–1937/38); anarchism; anarchism - Russia - 20th c.; USSR; Ukraine; bolshevism; repressions; political repression - Soviet Union